Fear of hypoglycemia is linked to poorer glycemic control and reduced quality of life in adults with type 1 diabetes - Mesa Díaz, Ángel Manuel; Belmonte Lomas, Samuel; Rodríguez de Vera Gómez, Pablo; Llanes González, María Victoria; Mateo Rodríguez, Carmen; Hidalgo Sotelo, Lucía; Martínez Brocca, María Asunción (Frontiers in Endocrinology, 2025)
AimAnalyze the influence of Fear of Hypoglycemia (FoH) on quality of life and glycemic control in adults with Type 1 Diabetes Mellitus (T1D) who use Flash Glucose Monitoring (FGM)MethodsA cross-sectional study was conducted with 173 adults with T1D. FoH was assessed using the FH15 questionnaire, and quality of life was evaluated using the Spanish Diabetes Quality of Life questionnaire (EsDQOL). Glycemic control was analyzed through FGM-derived metrics (Ambulatory Glucose Profile) and HbA1c. Multivariate multiple linear regression models were developed to analyze the adjusted impact of FoH on quality of life and time in hyperglycemia.ResultsFoH was present in 42% of participants (FH15 ≥28). Patients with FoH exhibited significantly higher EsDQOL scores, reflecting poorer quality of life, and higher HbA1c levels (7.41% vs. 7.08%, p=0.012). FGM metrics revealed higher mean glucose, glucose management indicator (GMI) (p=0.008), and time in hyperglycemia >250 mg/dL (p=0.035) in the FoH group, with lower time in range 70–180 mg/dl (p=0.035). Hypoglycemia unawareness was more frequent in the FoH group (25.4% vs. 6.5%, p=0.011). The FH15 score functioned as an independent predictor of quality of life (β = 1.98 [1.58; 2.37]) and time in hyperglycemia (β = 0.39 [0.17; 0.61]) in the multiple linear regression models.ConclusionFoH is significantly associated with poor quality of life and worsened glycemic control in T1D patients, underscoring the need for systematic assessment and individualized interventions. FGM metrics, particularly time in hyperglycemia, may serve as valuable predictors of FoH. Comprehensive management strategies addressing both metabolic and psychological factors are essential for improving patient outcomes.